Photoperiodic Regulation of Shoot Apical Growth in Poplar - Triozzi, Paolo M.; Ramos-Sánchez, José M.; Hernández-Verdeja, Tamara; Moreno-Cortés, Alicia; Allona, Isabel; Perales, Mariano (Frontiers in Plant Science, 2018)
Woody perennials adapt their genetic traits to local climate conditions. Day length plays an essential role in the seasonal growth of poplar trees. When photoperiod falls below a given critical day length, poplars undergo growth cessation and bud set. A leaf-localized mechanism of photoperiod measurement triggers the transcriptional modulation of a long distance signaling molecule, FLOWERING LOCUS T (FT). This molecule targets meristem function giving rise to these seasonal responses. Studies over the past decade have identified conserved orthologous genes involved in photoperiodic flowering in Arabidopsis that regulate poplar vegetative growth. However, phenological and molecular examination of key photoperiod signaling molecules reveals functional differences between these two plant model systems suggesting alternative components and/or regulatory mechanisms operating during poplar vegetative growth. Here, we review current knowledge and provide new data regarding the molecular components of the photoperiod measuring mechanism that regulates annual growth in poplar focusing on main achievements and new perspectives.